Answer:
Option A) f(n)=-5-4n is correct.
The equation would produce the same sequence of numbers as the recursive formula is f(n)=-5-4n
Explanation:
Given that a=-9 and
![a_(n)=a_(n-1)-4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/c6sx3e4kzum8go56up3ocgfw58zsa3wcf0.png)
The recursive formula is
![a_(n)=a_(n-1)+d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b7x3hpqueom5ycf8kk6y1lxpor7zcvhk2q.png)
Therefore d=-4
Let
and d=-4
We can find
![a_(2),a_(3),...](https://img.qammunity.org/2021/formulas/mathematics/middle-school/15jefmpbfp6e4fj1zvwl88momud2ksvyy1.png)
![a_(2)=a_(1)+d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6zz2vcfkojx8kegyyoqs9g81nq84hxfiv3.png)
![=-9-4=-13](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qbjpls4w14ls9m88s4bdzpy43chp2kwh2w.png)
Therefore
![a_(2)=-13](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3ocf3ar7d8siwu3hoknxlzb7aayn78monc.png)
![a_(3)=a_(2)+d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2fei20auxk3lx3uxgdbzc0cld3e6wyu0q6.png)
![=-13-4=-17](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dv9bxsv1oraiuo4y7wewx85mtdy2rh9pe6.png)
Therefore
and so on.
Therefore the arithmetic sequence is
![{\{-9,-13,-17,...}\}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/19cptzdov3c49dxoad4nw3v1rnql5lz7z7.png)
Option A) f(n)=-5-4n is correct.
f(n)=-5-4n
put n=1 in f(n)=-5-4n
f(1)=-5-4(1)
=-9
Therefore f(1)=-9
put n=2 in f(n)=-5-4n
f(21)=-5-4(2)
=-5-8
Therefore f(2)=-13
put n=3 we get f(n)=-5-4n
f(3)=-5-4(3)
=-5-12
Therefore f(3)=-17 and so on .
Therefore the sequence is
![{\{-9,-13,-17,...}\}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/19cptzdov3c49dxoad4nw3v1rnql5lz7z7.png)
Therefore the equation would produce the same sequence of numbers as the recursive formula is f(n)=-5-4n